A Survey ot the Economics of Information Goods - Huang, Shu xuan (Université d'Ottawa | University of Ottawa, 2012)
The Internet has shaped our economic world into a completely new era with its speed of communication and the high degree of interaction that it generates between people. It has transformed the way we access information in the fields of business, education